ANALISIS PERTUMBUHAN LABA PADA INDUSTRI MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - K Bidin, Cici Rianti; Samudra, Suryadi; Risendy, Rian; Murad, Moh Ali; Lamusu, Faruq; Dewi, Puspita (Fakultas Ekonomi Universitas Alkhairaat, 2023)
This study aims to identify the profit growth of companies operating in the food and beverage industry during the period from 2017 to 2022. The research employs a quantitative descriptive methodology and utilizes purposive sampling to select nine food and beverage industry companies listed on the Indonesia Stock Exchange. The results of this study reveal a positive profit growth trend, with an average profit growth of 19.4% from 2017 to 2022. However, in 2022, there was a significant decrease in profit growth due to the impact of the COVID-19 pandemic, which struck Indonesia from mid-2021 onwards. Keywords: Profit Growth, Quantitative Descriptive Methodology, Food And Beverage Industry